2004
DOI: 10.22358/jafs/67619/2004
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content of Bambara groundnut (<i>Vigna subterranea</i>) and the effects of its inclusion on the performance of growing broiler chickens and on egg production and quality

Abstract: Bambara groundnut (Vigna subterranea) was analysed for its nutrients content, and subsequently included into standard wheat-soyabean meal diets at the expense of wheat and soyabean meal. All diets had similar crude protein and total lipids contents and met the amino acids, minerals and vitamins requirements according to NRC (1994). In the 1 st experiment broiler chickens, kept in individual metabolic cages, were allotted to either a control, or one of 4 test groups, ten birds per treatment. The experiment last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In fact, as a "complete food" (Murevanhema and Jideani, 2013), which can be depended on for all the nutritional requirements for healthy livings, it is an important addition to the diet of poverty stricken folks who are unable to sustainably afford expensive animal protein sources (Food and Agriculture Organisation, n.d). It has also been reported that bambara groundnut has potentials for industrial purposes (Ibrahin and Ogunwusi, 2016, Atiku et al, 2004) and has been experimented with in feeding of livestock (Nji et al, 2003(Nji et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as a "complete food" (Murevanhema and Jideani, 2013), which can be depended on for all the nutritional requirements for healthy livings, it is an important addition to the diet of poverty stricken folks who are unable to sustainably afford expensive animal protein sources (Food and Agriculture Organisation, n.d). It has also been reported that bambara groundnut has potentials for industrial purposes (Ibrahin and Ogunwusi, 2016, Atiku et al, 2004) and has been experimented with in feeding of livestock (Nji et al, 2003(Nji et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%